The rationality of consumers' inflation expectations: survey-based evidence for the euro area - Magnus Forsells; Geoff Kenny (European Central Bank (ECB), 2002)
This paper uses survey data to assess consumers' inflation expectations in the euro area. The probability approach is used to derive quantitative estimates of inflation expectations from the European Commission's Consumer Survey. The paper subsequently analyses the empirical properties of the estimated inflation expectations by considering the extent to which they fulfil some of the necessary conditions for rationality. The results suggest an intermediate form of rationality. In particular, the surveyed expectations are an unbiased predictor of future price developments and they incorporate - though not always completely - a broad set of macroeconomic information. In addition, although persistent deviations between consumers' expectations and the rational outcome have occurred, consumers are shown to rationally adjust their expectations in order to eventually 'weed out' any systematic expectational errors. Interestingly, perhaps reflecting changes in the monetary regime, there is also evidence of 'growing' rationality over the 1990s compared with the 1980s.
Keywords: D12; D84; E31; 330; euro area; inflation expectations; Rationality; Surveys